Adoption of technology on E-learning effectiveness - Zarina Denan; Zarina Abdul Munir; Rahayu A. Razak; Kardina Kamaruddin; Veera Pandiyan Kaliani Sundram (Institute of Advanced Engineering and Science, 2020)
The incorporation of E-learning in both private and public tertiary education can help expedite the learning process. The utilization of fast-paced technology with E-learning also allows for a more flexible and convenient learning process. E-learning platforms can be accessed anywhere as long as there is an internet connection, including at home, the workplace, restaurants or while travelling. This allows for the benefit of distance learning. As such, the current study aims to examine the factor effectiveness of E-learning based on three variables, namely technology, instructors’ characteristics and students’ characteristics and their impact on distance learning. The education system has greatly evolved from the use of apparatus such as chalk and blackboards to the modern use of projectors to conduct lessons. In the current age, E-learning will have an effect on both instructors and teaching technology, aside from the students themselves. As an example, students are expected to know how to utilize these systems in their lessons, instructors must receive training in E-learning systems management and in terms of technology, the E-learning systems must be updated and operated using the most recent upgrades. E-learning is also cost-efficient, less time consuming and reduces the burden on both students and educators.